Stunting on children under five years on family of beneficiary family hope program in Wonogiri district, Central Java - Harjatmo, Titus Priyo; Herlianty, Maria Poppy; Hartono, Antonius Sri (International Journal Of Community Medicine And Public Health, 2018)
Background: The nutritional status of infants and toddlers is one indicator of public nutrition, and even has developed into one of the indicators of health and welfare. Basic Health Research (Riskesdas) in 2013 showed that 37,2% children under five suffering from nutritional status is stunting. One of the efforts that have been made by the Indonesian government to reduce malnutrition in infants and toddlers is through a program that is integrated with the health sector namely Conditional Cash Transfer Program (Program Keluarga Harapan). The specific objectives were to identify the characteristics of families recieve Conditional Cash Transfer Program and analysis stunting children under five years in families receiving Conditional Cash Transfer Program in Baturetno subdistric, Wonogiri district. Methods: The study was conducted in the subdistrict of Baturetno, Wonogiri district and has collected a total of 112 infants of families Conditional Cash Transfer Program participants. Sampling of children under five years was done purposively. This study was conducted from July to August 2017. Results: The proportion of children who stunting quite high at 33.0% higher than the results of the Nutritional Status Monitoring in 2016 amounted to 27.5%. If stunting is associated with the age group of stunting problems occur in all age groups in the amount of 31.3% in under 23 months and 34.3% at 23 months upwards of 31.3% children under five short, as much as 25.0% children under five are overweight according to height (weight for height) is normal and thus potentially becoming obese. Conclusions: The implementation of weight monitoring should be monitored the height of children under five in the hope family program.